Automatic digital ECG signal extraction and normal QRS recognition from real scene ECG images. (April 2020) - Wang, Shuang; Zhang, Shugang; Li, Zhen; Huang, Lei; Wei, Zhiqiang
Highlights: An Adaptive Filter Algorithm (AFA) is proposed in this paper for uneven illumination problem. The AFA method relieves the effect of uneven illumination that commonly exists in real-scene ECG image to a large extent. A channel dependent hierarchical scheme for automatic ECG binary image extraction from ECG image in real scene is introduced. The two layers aim separately at gridline removing and illumination relieving depending on different channels' properties, but they also complement each other and finally generate a good denoised ECG signal. 1D ECG signal extraction is based on ECG binary image and low difference between extracted value and real value shows excellent ability of the proposed approach. We also bring forward a new QRS recognition method using fused image features. This provides a way to utilize spatial relationships of special points to assist in disease diagnose. A candidate point set strategy is used for further computing optimization. Abstract: Background and objective: Electrocardiogram (ECG) is one of the most important tools for assessing cardiac function and detecting potential heart problems. However, most of the current ECG report records remain on the paper, which makes it difficult to preserve and analyze the data. Moreover, paper records could result in the loss significant data, which brings inconvenience to the subsequent clinical diagnosis or artificial intelligence-assisted heart health diagnosis. Taking digital pictures is an intuitive way of preserving these files and can be done simply using smartphones or any other devices with cameras. However, these real scene ECG images often have some image noise that hinders signal extraction. How to eliminate image noise and extract ECG binary image automatically from the noisy and low-quality real scene images of ECG reports is the first problem to be solved in this paper. Next, QRS recognition is implemented on the extracted binary images to determine key points of ECG signals. 1D digital ECG signal is also extracted for accessing the exact values of the extracted points. In light of these tasks, an automatic digital ECG signal extraction and normal QRS recognition from real scene ECG images is proposed in this paper. Methods: The normal QRS recognition approach for real scene ECG images in this paper consists of two steps: ECG binary image extraction from ECG images using a new two-layer hierarchical method, and the subsequent QRS recognition based on a novel feature-fusing method. ECG binary image extraction is implemented using sub-channel filters followed by an adaptive filtering algorithm. According to the ratio between pixel and real value of ECG binary image, 1D digital ECG signal is obtained. The normal QRS recognition includes three main steps: establishment of candidate point sets, feature fusion extraction, and QRS recognition. Two datasets are introduced for evaluation including a real scene ECG images dataset and the public Non-Invasive Fetal Electrocardiogram Database (FECG). Results: Through the experiment on real scene ECG image, the F1 score for Q, R, S detection is 0.841, 0.992, and 0.891, respectively. The evaluation on the public FECG dataset also proves the robustness of our algorithm, where F1 score for R is 0.992 (0.996 for thoracic lead) and 0.988 for thoracic S wave. Conclusions: The proposed method in this article is a promising tool for automatically extracting digital ECG signals and detecting QRS complex in real scene ECG images with normal QRS.